Réponses

Meilleure réponse !
2013-04-07T12:38:08+02:00
X-1=(3x-4)/2
(2(x-1))/2=(3x-4)/2
(2x-2)=3x-4
2x-3x=-4+2
-x=-2
X=2

1-(2-3x)/5=2x
5/5-(2-3x)/5=2x
(5-2-3x)/5=2x
(3-3x)/5=10x/5
3=10x+3x
3=13x
X=3/13
2013-04-07T12:43:31+02:00

x - 1 = 3x -4   = 2x -2  = 3x  -4  

             2              2             2

2x-2 = 3x-4

2x -3x = 2 -4

-x = -2

x = 2

 

1 - 2-3x = 2x = 5 -2 -3x  = 10x

       5                 5    5           5

                         5 -2 -3x = 10x

                         3 -3x = 10 x

                          -3x = -3 +10x

                         -3x -10x = -3

                           -13 x = -3

                               x = -3/13